Influence of dietary components on the risk of gallstone formation - Sawczuk, Marcelina; Ptak, Jakub; Miśkiewicz, Marek; Marcinkowska, Jagoda; Perłowski, Jakub; Teska, Victoria; Koczkodon, Karolina; Noga, Rafał; Krompiewski, Mariusz; Herc, Adrian (Journal of Education, Health and Sport, 2024)
Gallbladder disease is a common condition in the population that has a negative impact on quality of life. The development of gallstones is influenced by both non-modifiable factors such as genetics, age, gender and modifiable risk factors including physical activity, body weight, diet. Dietary factors affecting the occurrence of the disease are difficult to capture in clinical studies, but the effect of certain substances on the development of gallstones has been proven. Positive risk factors include a high-calorie diet, obesity, increased intake of carbohydrates, saturated fatty acids, small amounts of fiber ingested. Moderate alcohol consumption reduces the risk of gallstones. Coffee may reduce the risk of the disease, but results are inconclusive. Inverse risk factors include consumption of monounsaturated fatty acids, consumption of nuts, olive oil, n-3 PUFA found in fish oil, vitamin C supplementation. No clear effect of consuming large amounts of dietary cholesterol can be established. The type of protein consumed also matters - vegetable protein reduces the risk of gallstones, animal protein has no such effect. Better understanding of dietary risks of cholelithiasis may help in future disease prevention.